Perfil alimentar e sociodemográfico de pacientes com tuberculose pulmonar - SOUZA, Fapríscia Gomes de (2023)
Pulmonary tuberculosis is a contagious infectious disease that affects around 10 million people worldwide each year, its condition can be aggravated by elevated sérum glucose and lipid levels. This study aims to describe the sociodemographic, lipid and glycemic profile of adults undergoing treatment for pulmonary tuberculosis. This is a crosssectional study, with adults seen at the Basic Health Unit in the neighborhood of Guamá-Belém, in Belém-Pa. Variables were collected regarding the sociodemographic profile (gender, age and education) and the biochemical profile (total cholesterol and fractions and blood glucose). In total, 105 patients participated in the study, most of them male, aged between 40 and 59 years and schooling from 0 to 9 years of study. Regarding the biochemical profile, there was a reduction in the levels of the median values of total cholesterol and fractions in the last month of treatment. There was na increase in median glycemic values between the initial and final period of treatment for pulmonary tuberculosis.